Physicochemical properties and penetration into dentinal tubules of calcium hypochlorite with surfactants - Coaguila-Uerena, Hernan [UNESP]; Ramos, Julia Da Silva Toledo Ana Paula; Faria, Gisele [UNESP] (My University, 2022)
The aim was to assess the physicochemical properties and the penetration into dentinal tubules of calcium hypochlorite solution [Ca(0CI)2], with or without surfactants. The surfactants benzalkonium chloride, cetrimide, Tween 80 and Triton X-100 were mixed at different concentrations with sodium hypochlorite solution (NaOCI), Ca(0CI)2 and distilled water (control). Once the critical mieellar concentration (CMC) of the surfactants in Ca(0CI)2 and NaOCI was determined, pH, free chlorine, surface tension and free calcium ions were evaluated. The penetration into dentinal tubules of NaOCI and Ca(0CI)2, with or without benzalkonium chloride and Triton X-100 [surfactants that promoted the lowest surface tension of Ca(0CI)2], was assessed using human premolars stained with crystal violet. The statistical tests were one-way ANOVA and Tukey's post-test, Kruskal-Wallis and Dunn's post-test, two-way ANOVA and Bonferroni's post-test, and t-test; depending on the assay. The addition of surfactants reduced the surface tension of NaOCI and Ca(0CI)2, and did not alter the pH or the free available chlorine of either solution. The addition of all surfactants increased the availability of free calcium ions in Ca(0CI)2, especially benzalkonium chloride. Ca(0CI)2 exhibited lower penetration into dentinal tubules than NaOCI, and the addition of surfactants did not improve the penetration of Ca(0CI)2, but did increase the penetration of NaOCI. It can be concluded that the addition of surfactants to Ca(0CI)2 did not increase the penetration into dentinal tubules, but it did promote lower surface tension, without changing the pH or free available chlorine values, and higher availability of free calcium ions in Ca(0CI)2.
Keywords: Calcium hypochlorite; Dentin permeability; Endodontics; Sodium hypochlorite; Surface-active agents